An Overview of Analytical Techniques Employed to Evidence Drug-DNA Interactions. Applications to the Design of Genosensors - González-Ruiz, Víctor; Olives, Ana I.; Martín, M. Antonia; Ribelles, Pascual; Ramos, M. Teresa; Menéndez, J. Carlos (IntechOpen, 2011)
None